Shoulder laxity and traumatic shoulder instability in professional rugby players. Issue 2 (20th January 2011) - Sivardeen, Ziali; Cheng, Shih Chung; Buchanan, Donald; Hulse, David; Fairbairn, K Julia; Kemp, Simon Patrick Thomas; Brooks, John Huw Meirion; Wallace, William Angus
Abstract : Objective: This study aimed to see whether the risk of shoulder dislocation is associated with innate shoulder laxity, in professional rugby players. Methodology: We performed a pilot study where we validated techniques we used in the study and subsequently gained ethics committee approval. We visited all the premiership rugby clubs in England and assessed 169 professional rugby players with no history of shoulder instability and 46 players with clinical instability symptoms in one shoulder. We assessed shoulder laxity by means of clinical evaluation, questionnaires and ultrasound. Previous studies have shown no difference in shoulder laxity in left and right shoulders in normal individuals. We therefore compared the laxity in the uninjured shoulder of players with a previous history of dislocation, with the shoulders of players with no history of shoulder injury. Data was analysed by unpaired t tests. Results: The results showed there was no significant difference between the left and right shoulders in players with no history of instability (p>0.05). Players with a history of instability had a significantly higher shoulder translation in their normal shoulder than uninjured players (p<0.05). Players with an anterior laxity of at least 4 mm had a 50% chance of sustaining a dislocation. There was no correlation between, the age of the player, dominant hand or position played and the incidence of increased laxity. Conclusions: This is the first study looking at laxity and the risk of shoulder dislocations in sportsmen involved in a high contact sport. These results support the hypothesis that rugby players with 'lax' shoulders are more likely to sustain a dislocation or subluxation injury to one of these lax shoulders in their sport. We believe preseason screening and targeted training may play a role in identifying those at risk and may decrease the incidence of dislocations.